2009
DOI: 10.1007/s10728-008-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

Trust but Verify: The Interactive Effects of Trust and Autonomy Preferences on Health Outcomes

Abstract: Patients' trust in their physicians improves their health outcomes because of better compliance, more disclosure, stronger placebo effect, and more physicians' trustworthy behaviors. Patients' autonomy may also impact on health outcomes and is increasingly being emphasized in health care. However, despite the critical role of trust and autonomy, patients that naïvely trust their physicians may become overly dependent and lack the motivation to participate in medical care. In this article, we argue that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 70 publications
(76 reference statements)
0
21
0
1
Order By: Relevance
“…Moreover, in the health communication literature, specifically, it has been shown that trust in physicians is associated with better health outcomes because trusting patients are more likely to adhere to treatment recommendations (Lee & Lin, 2009;Thom, Hall & Pawlson, 2004). Similarly, trust in media has also been associated with health-related outcomes.…”
Section: Online Health Informationmentioning
confidence: 99%
“…Moreover, in the health communication literature, specifically, it has been shown that trust in physicians is associated with better health outcomes because trusting patients are more likely to adhere to treatment recommendations (Lee & Lin, 2009;Thom, Hall & Pawlson, 2004). Similarly, trust in media has also been associated with health-related outcomes.…”
Section: Online Health Informationmentioning
confidence: 99%
“…This phenomenon may be due to the paternalistic nature of the patient-physician relationship in Taiwan. 46,47 Moreover, participants had a similar passive attitude toward their involvement in the medical decision-making process regardless of dealing with conventional medical clinicians or TCM practitioners. In contrast, CAM users from Western countries tend to participate more and be more active in medical decision making.…”
Section: Social Considerations Of Using Tcm During Chemotherapymentioning
confidence: 99%
“…15,44,48 It is possible that the naive trust and overdependence on physician in Chinese culture may have caused the difference. 46 …”
Section: Social Considerations Of Using Tcm During Chemotherapymentioning
confidence: 99%
“…16 This is considered appropriate because of both, the costs and dangers of blind trust wherein there is a risk of corruption, exploitation, or domination particularly for those with a lack of resources, as well as due to the imperatives related to patient autonomy preferences. 18 Another important way of understanding trust relations in the context of healthcare is to distinguish between interpersonal trust – the trust between individual patient and individual care provider/doctor, and institutional trust, which relates primarily to trust in the medical profession or in the healthcare system. Some authors refer to the latter as systems trust, which signifies “accountability and the checks and balances and systems that maintain fairness, preventing incompetence or malign intent”(p. 9).…”
mentioning
confidence: 99%